Toward effective partially protected areas in Tanzania: a review on experiences from Ugalla ecosystem - Wilfred, Paulo (Tanzania Journal of Science, 2021)
Tanzania is understandably concerned about the deterioration of its partially protected areas (PPAs, e.g. game controlled and open areas) due to unauthorised resource use activities. Its 2007 wildlife policy recognises that PPAs are managed as buffer zones so they provide a cushion against land use impacts on core protected areas, and support local livelihoods. Ensuring effective protection of PPAs is especially timely given the fact that Tanzania’s human population is now large and growing rapidly, with rising demand for natural resources, and that protected areas are becoming increasingly isolated. This paper draws insight from research activities in Ugalla ecosystem, western Tanzania, to draw attention to the threats facing PPAs in the country, and discuss strategies for addressing them. Ugalla ecosystem consists of Ugalla Game Reserve and the surrounding vast PPAs that experience logging, poaching, forest invasions, and pressure from other livelihood activities. Consequently, wildlife populations are contracting and habitats are quickly disappearing. Law enforcement, participatory conservation and improving household livelihoods are key to effective deterrence of unauthorised activities; increasing access to family planning services would enable people to better manage the size of their families, and thus ease pressure on resources due to the growth of local populations; community outreach and engagement would help win local support for conservation; effective wildlife management areas would benefit both local community and conservation; monitoring is critical to informing conservation actions; introducing some strict protectionism would slow persistent offtake. Lastly, local conservation authorities should be supported to address the underlying causes of conservation problems in the PPAs. Keywords: partially protected areas, unauthorised activities, impacts, interventions, Ugalla, Tanzania